1994
DOI: 10.1007/bf00241095
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia induces release of atrial natriuretic peptide in rat atrial tissue: a role for this peptide during low oxygen stress

Abstract: A variety of different factors have been shown to induce release of atrial natriuretic peptide from atrial tissue. Among these, stretching of atrial myocytes is considered the most important. In a recent study we showed that atrial natriuretic peptide increased cGMP and reduced lactate accumulation during hypoxia in rat ventricular myocardium. This suggests that atrial natriuretic peptide has a beneficial metabolic effect during hypoxia and raises the question whether hypoxia alone induces release of atrial na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Isolated rat hearts increase ANP and BNP with an acute (30 min) exposure to normobaric hypoxic [2]. Indeed, even just 10 min of normobaric hypoxia can induce ANP release in both anaesthetized rats [3] and rat atrial and ventricular tissue [4], with the steepest rise in ANP after the first 10 min of exposure [4]. In humans, ANP has been found to rise acutely after breathing a hypoxic gas mixture (10% O 2 ) for only 10 min [5].…”
Section: Introductionmentioning
confidence: 99%
“…Isolated rat hearts increase ANP and BNP with an acute (30 min) exposure to normobaric hypoxic [2]. Indeed, even just 10 min of normobaric hypoxia can induce ANP release in both anaesthetized rats [3] and rat atrial and ventricular tissue [4], with the steepest rise in ANP after the first 10 min of exposure [4]. In humans, ANP has been found to rise acutely after breathing a hypoxic gas mixture (10% O 2 ) for only 10 min [5].…”
Section: Introductionmentioning
confidence: 99%
“…1996, Zhang et al . 2004) and from isolated cell lines of human cardiac origin (Ljusegren & Andersson 1994, Klinger et al . 2001, Hopkins et al .…”
mentioning
confidence: 99%
“…hypoxia has also proved to be a powerful stimulus for the release of natriuretic peptides from the rodent heart (Baertschi et al 1986, Lew & Baertschi 1989, Uusimaa et al 1992a,b, Chen et al 1993, Arad et al 1994, T oth et al 1994, Focaccio et al 1995, Svorak et al 1996, Zhang et al 2004) and from isolated cell lines of human cardiac origin (Ljusegren & Andersson 1994, Klinger et al 2001, Hopkins et al 2004, Casals et al 2009). Also, both the A-and B-type peptides have a hypoxia-responsive element in the promoter sequence of their respective genes (Chun et al 2003, Luo et al 2006 and hypoxia has been shown to be a direct and sufficient stimulus for the transcription of the gene encoding B-type peptide (Weidemann et al 2008).…”
mentioning
confidence: 99%
“…Isolated rat hearts increase ANP and BNP with an acute (30 minutes) hypoxic exposure [27]. Indeed, even just 10 minutes of hypoxic exposure can induce ANP release in both isolated rat atrial tissue [28] and in anaesthetized rats [29].…”
Section: The Dual Natriuretic Peptides Of the Heart: Anp And Bnpmentioning
confidence: 99%